The Hermeneutics of Grace: Discerning the Bible's Single Plot" - McCann, J. Clinton (Interpretation, 2003)
The Bible offers a unified portrayal of a God who is essentially gracious, merciful, and loving. The discernment of the Bible's “single plot”—the hermeneutics of grace—has profound social and ethical implications.